Investigation of Strength Concrete Materials Using Pozzolanic Additives - Aulia, Teuku Budi; Fachruddin, Fachruddin; Hasan, Muttaqin; Yusra, Andi (Applied mechanics and materials, 2024)
In the study, pozzolanic materials serve as replacements for additives, namely Palm Shell Ash (PSA), Coal Fly Ash (CFA), and Rice Husk Ash (RHA). The purpose of the study is to determine the optimum proportion of additives used in high-performance concrete. The addition of 15% PSA resulted in a strength of 69.227 MPa over a test period of 56 days, while the addition of 15% CFA yielded a strength of 69.369 MPa, and the addition of 5% RHA resulted in a strength of 59.984 MPa. The maximum concrete strength is achieved by adding 15% PSA. Correlation analysis between stress-strain indicates that aggregates exhibit higher strength compared to cement paste, mortar, and concrete, highlighting the relationship between the aggregate, cement paste, mortar components, and concrete as a composite material. Aggregate strength values found to be the highest among concrete, cement paste, and mortar, indicating that cement paste contributes the least to the strength of concrete, followed by mortar as concrete reinforcement. The results suggest that aggregates remain the primary strength component supporting concrete. The finding indicates that the relationship between the basic substances in this study aligns closely with existing theory. Moreover, it suggests that all concrete materials with pozzolan variants can classified as high-quality concrete. The optimum percentage is obtained by adding 15% palm shell ash, resulting in the highest compressive strength compared to counterparts and test objects with other types of pozzolan additions. The relationships between the constituents of concrete demonstrate that aggregates continue to be important contributors to concrete strength, with the cement paste contributing the least. Concrete strength values fall between those of aggregates and those of cement and mortar pastes.